(untitled) (MMIT Proceedings, 2025)
The article is a commented translation from Arabic of the essay by the greatest mathematician of the 16th century Baha ad-Din al Amili “The Essence of Arithmetic”. The paper also provides a historical and comparative analysis of the mathematical chapters of encyclopedias of that period using various sources.